Stratified delirium risk using prescription medication data in a state-wide cohort - McCoy, Thomas H. (Gen Hosp Psychiatry, 2021)
OBJECTIVE: Delirium is a common condition associated with increased morbidity and mortality. Medication side effects are a possible source of modifiable delirium risk and provide an opportunity to improve delirium predictive models. This study characterized the risk for delirium diagnosis by applying a previously validated algorithm for calculating central nervous system adverse effect burden arising from a full medication list. METHOD: Using a cohort of hospitalized adult (age 18-65) patients from the Massachusetts All-Payers Claims Database, we calculated medication burden following hospital discharge and characterized risk of new coded delirium diagnosis over the following 90 days. We applied the resulting model to a held-out test cohort. RESULTS: The cohort included 62,180 individuals of whom 1.6% (1,019) went on to have a coded delirium diagnosis. In the training cohort (43,527 individuals), the medication burden feature was positively associated with delirium diagnosis (OR=5.75, 95% CI 4.34–7.63) and this association persisted (aOR=1.95; 1.31–2.92) after adjusting for demographics, clinical features, prescribed medications, and anticholinergic risk score. In the test cohort, the trained model produced an area under the curve of 0.80 (0.78–0.82). This performance was similar across subgroups of age and gender. CONCLUSION: Aggregating brain-related medication adverse effects facilitates identification of individuals at high risk of subsequent delirium diagnosis.